H2 adsorption on K decorated germanene surface: An ab-initio investigation - Rojas, Kurt Irvin M. (Animo Repository, 2016)
© 2016 IOP Publishing Ltd. The hydrogen physisorption on K-decorated germanene as potential hydrogen storage was calculated using DFT through VASP. Various approach sites and initial orientations for the H2 were considered for the adsorption. It was found that H2, with a vertical orientation, approaching the valley site was the preferred approach configuration with an associated adsorption energy within the van der Waals interaction energy range. Also, complete site-to-site migration was hindered by some potential barrier inherent in the material suggesting multiple metastable configurations.